Comparative evaluation of the efficacy of diode laser, EndoActivator, passive ultrasonic irrigant, and manual irrigation activation systems in debridement of root canal isthmus: An in vitro study - Arun Kurian Varghese; S V Satish; Basavana Gowda; Roshan Uthappa; Ashwini M Patil (Wolters Kluwer Medknow Publications, 2022)
Objective: This study aimed to compare the efficacy of diode laser, EndoActivator, passive ultrasonic irrigation (PUI), and manual dynamic activation (MDA) in the debridement of root canal isthmus using a stereomicroscope. Materials and Methods: A total of 65 extracted mandibular first molars were selected for the study. The access cavity preparation was done and the working length was determined. All teeth were prepared using ProTaper rotary system up to F2. The samples were randomly divided into five groups (n = 13) used in the study. Group 1: Diode laser (n = 13): samples were irrigated using a diode laser having a wavelength of 980 nm. Group 2: EndoActivator (n = 13): the samples were irrigated using EndoActivator sonic device. Group 3: PUI (n = 13): samples were irrigated using an ultrasonic device. Group 4: MDA (n = 13): samples were irrigated manually by placing a master gutta-percha cone of F2 size. Group 5: Conventional needle irrigation (n = 13): no activation of irrigant. Following irrigant activation, the mesial roots were sectioned 4 mm from the apex and the isthmus cleanliness was observed under a stereomicroscope at ×20. Statistical analysis was done using ANOVA and post hoc Tukey's test. Results: EndoActivator showed the least amount of debris when compared to diode laser, passive ultrasonic irrigant, and MDA. MDA showed more amount of debris at the isthmus level. Conclusion: EndoActivator showed the least amount of debris at the isthmus level of mandibular molars when compared to diode laser, passive ultrasonic irrigant, and MDA.